2023
DOI: 10.1371/journal.pone.0287372
|View full text |Cite
|
Sign up to set email alerts
|

Global depression in breast cancer patients: Systematic review and meta-analysis

Akbar Javan Biparva,
Samira Raoofi,
Sima Rafiei
et al.

Abstract: Background Breast cancer is known as one of the most common diseases among women, the psychological consequences of which are common in women and affect various aspects of their lives, so this study aims to investigate the prevalence of depression among women with breast cancer globally. Method The present meta-analysis was performed by searching for keywords related to breast cancer and depression in 4 main databases: PubMed, Embase, Web of Sciences and Scopus in the period of January 2000 to November 2021 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Overall, the findings of our research show a high burden of mental disorders among the general-adult population in SA, with even higher prevalence among specific population subgroups. These findings are also supported by reviews published since our searches were carried out (Manna et al, 2022; Palfreyman and Gazeley, 2022; Al-Mamun et al, 2023; Javan Biparva et al, 2023). Our results highlight an urgent need for countries in SA to formulate and implement both clinical and policy measures for the prevention and early treatment of mental disorders and intentional self-harm.…”
Section: Discussionsupporting
confidence: 85%
“…Overall, the findings of our research show a high burden of mental disorders among the general-adult population in SA, with even higher prevalence among specific population subgroups. These findings are also supported by reviews published since our searches were carried out (Manna et al, 2022; Palfreyman and Gazeley, 2022; Al-Mamun et al, 2023; Javan Biparva et al, 2023). Our results highlight an urgent need for countries in SA to formulate and implement both clinical and policy measures for the prevention and early treatment of mental disorders and intentional self-harm.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, with the growth of age, women suffering from breast cancer have an increased risk of depression. Compared with developed regions, the prevalence of depression in breast cancer patients in developing countries is higher [20] .Depression is closely related to breast cancer patients' physical defects, disease severity and chronic pain. In addition, if breast cancer and depression occur at the same time, patients will experience more severe pain, extreme fatigue, decreased survival rate and quality of life [21] .In a recent meta-analysis, the results con rmed that cancer patients with depressive symptoms have a 25% higher mortality rate, and psychological intervention can effectively improve the 12 month survival rate [22] .That is to say, even if cancer patients receive effective anti-tumor treatment, psychological factors such as depression and anxiety still lead to poor prognosis and decreased living standards.…”
Section: Discussionmentioning
confidence: 98%
“…Among patients with metastatic breast cancer in Germany, their EQ-VAS scores were significantly associated with single EQ-5D-5L items and the total score [ 42 ]. Furthermore, breast cancer patients usually suffer from mental health and psychological issues [ 43 45 ]. Previous studies demonstrated that breast cancer patients suffering from depression, anxiety, and stress also had lower health-related quality of life [ 11 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%